Towards a movement-friendly city: lessons from activity scans of five neighbourhoods in Antwerp, Belgium - Devos, Tim; Van Acker, Maarten; Vandevoorde, Jakob; Rybels, Stijn (Journal of urban design, 2023)
This paper describes the results of a research project in Antwerp, Belgium, aimed at developing a spatial analysis approach ('activity scan') assessing how the urban fabric on a neighbourhood scale can encourage physical activity and active transport. By outlining a set of recurring spatial challenges and describing the developed innovative toolkit, the research responds to the necessity for design-oriented insights on how to promote active travel and instigate concrete interventions. By critically analysing this co-creative research trajectory, this article emphasizes the need for an interdisciplinary dialogue on what contributes to a movement-friendly urban environment.